2018
DOI: 10.3389/fneur.2018.00845
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiological Characteristics of Epilepsy in the Province of Khyber Pakhtunkhwa, Pakistan

Abstract: Previous studies have shown that Khyber Pakhtunkhwa, Pakistan has a high incidence of epilepsy and a high proportion of low socioeconomic background and high treatment gap. Considering the changes over the past 20 years little is known about the current epidemiological characteristics of epilepsy in Khyber Pakhtunkhwa, Pakistan. The current study was focused to find the impact of various contributing factors on the clinical response to anti-epileptic drugs in the KP population, Pakistan. A total of 315 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In India, alcohol consumption is largely restricted to males, particularly among the lower socioeconomic strata. Similar sex ratios have been reported in previous studies [ 6 - 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…In India, alcohol consumption is largely restricted to males, particularly among the lower socioeconomic strata. Similar sex ratios have been reported in previous studies [ 6 - 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…In a Pakistani study, Jawaid et al 11 found a mean age of 21.4 ±3.2 years. In studies in SSA and other developing countries, the mean age of epileptic patients ranges from 15 to 20 years, 12,13 unlike in developed countries where epilepsy has a bimodal distribution (i.e. one peak after a few years of birth and the other peak occurs after 65 years).…”
Section: Discussionmentioning
confidence: 99%
“…Most patients from this study belonged to low socio-economic status. The characteristics associated with poor response to management included low socio-economic status, non-compliance to therapy and generalized onset tonic-clonic seizures [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Head injuries can also cause seizures either immediately or many years later. In the elderly, stroke and neurodegenerative conditions frequently lead to seizures [4].…”
Section: Introductionmentioning
confidence: 99%